Peran Media Sosial dalam Fenomena Viralitas: Studi Pada Akun Tik Tok @Bundacorlaofficials - Nilam Yunita Sari; Anita Reta Kusumawijayanti (Perspektif Administrasi Publik dan hukum, 2024)
Viral describes something that is often associated with content on social media. Usually synonymous with something or information that is interesting and spreads quickly. Viral content creates a desire for social media users to repost the content. In the digital era, social media seems to be a basic need for sharing information, photos or videos. This research discusses the virality of Bunda Corla, a public figure known to the public through her content on TikTok. The TikTok account @bundacorlaofficials is a medium of communication with its followers to share information about Bunda Corla's daily activities. This study using a qualitative approach examines the role of TikTok in the virality phenomenon of Bunda Corla. Data collection used interviews, literature studies and observations on the TikTok account @bundacorlaofficials as the main source of research data. Research using new media theory by Pierre Levy and research results from Deza and Parikh regarding measuring the virality of content which is influenced by views, up votes, down votes and share value. It was revealed that content becomes viral if it is shared repeatedly and spreads on social media.